PENGARUH KREDIT BERMASALAH TERHADAP SISA HASIL USAHA PADA KOPERASI SERBA USAHA (KSU) BINA WARGA BANDUNG PERIODE 2014-2018 - Sugianto Ikhsan; Gunardi; Mira Veranita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of non-performing loans on theResidual Income (SHU) of the Multipurpose Cooperative (KSU) Bina WargaBandung from 2014 to 2018. This study uses a descriptive and quantitativeapproach. Pearson Product Moment Correlation Analysis and coefficient ofdetermination are used in data analysis techniques. Data collection techniques usedin this research include literature study, field study, and documentation, while thepopulation is taken from financial reports and purposive sampling. Variables X andY have a very strong relationship, as indicated by the Pearson Product Momentcorrelation coefficient of -0.953, in accordance with the findings of this study. Nonperforming loans are 90.8 percent of income (SHU) at KSU Bina Warga Bandungaccording to the coefficient of determination, while the remaining 9.2 percent is dueto other factors not examined.